Exercise and incidence of myocardial infarction, stroke, hypertension, type 2 diabetes and site-specific cancers: prospective cohort study of 257 854 adults in South Korea. Issue 3 (13th March 2019) - Kim, Youngwon; Sharp, Stephen; Hwang, Semi; Jee, Sun Ha
Abstract : Objective: The objective of this study was to examine the longitudinal associations of exercise frequency with the incidence of myocardial infarction, stroke, hypertension, type 2 diabetes and 10 different cancer outcomes. Design: A prospective cohort study. Setting: Physical examination data linked with the entire South Korean population's health insurance system: from 2002 to 2015. Participants: 257 854 South Korean adults who provided up to 7 repeat measures of exercise (defined as exercises causing sweat) and confounders. Primary outcome measures: Each disease incidence was defined using both fatal and non-fatal health records (a median follow-up period of 13 years). Results: Compared with no exercise category, the middle categories of exercise frequency (3–4 or 5–6 times/week) showed the lowest risk of myocardial infarction (HR 0.79; 95% CI 0.70 to 0.90), stroke (HR 0.80; 95% CI 0.73 to 0.89), hypertension (HR 0.86; 95% CI 0.85 to 0.88), type 2 diabetes (HR 0.87; 95% CI 0.84 to 0.89), stomach (HR 0.87; 95% CI 0.79 to 0.96), lung (HR 0.80; 95% CI 0.71 to 0.91), liver (HR 0.85; 95% CI 0.75 to 0.98) and head and neck cancers (HR 0.76; 95% CI 0.63 to 0.93; for 1–2 times/week), exhibiting J-shaped associations. There was, in general, little evidence of effect modification by body mass index, smoking, alcohol consumption, family history of disease and sex in these associations. Conclusions: Moderate levels of sweat-inducing exercise showed the lowest risk of myocardial infarction, stroke, hypertension, type 2 diabetes, stomach, lung, liver and head and neck cancers. Public health and lifestyle interventions should, therefore, promote moderate levels of sweat-causing exercise as a behavioural prevention strategy for non-communicable diseases in a wider population of East Asians.